Answer:
Sentence Fram: I found x-intercept by substitute y by 0 and I found y-intercept by substitute x by 0
x-intercept = (6, 0), y-intercept = (0, -3) ⇒ C
Step-by-step explanation:
- To find the x-intercept of a line, equate y in its equation by 0
- To find the y-intercept of a line, equate x in its equation by 0
∵ The equation of the graph is 6x - 12y = 36
→ Equate y by 0 to find x
∵ y = 0
∴ 6x - 12(0) = 36
∴ 6x - 0 = 36
∴ 6x = 36
→ Divide both sides by 6 to find x
∴ x = 6
∴ The x-intercept = (6, 0)
→ Equate x by 0 to find y
∵ x = 0
∴ 6(0) - 12y = 36
∴ 0 - 12y = 36
∴ -12y = 36
→ Divide both sides by -12 to find y
∴ y = -3
∴ The y-intercept = (0, -3)
∴ Sentence Fram: I found x-intercept by substitute y by 0 and I found
y-intercept by substitute x by 0
∴ x-intercept = (6, 0), y-intercept = (0, -3)